The Will to Empower : Democratic Citizens and Other Subjects - Cruikshank, Barbara (Ithaca, NY : Cornell University Press, 1999)
How do liberal democracies produce citizens who are capable of governing themselves? In considering this question, Barbara Cruikshank rethinks central topics in political theory, including the relationship between welfare and citizenship, democracy and despotism, and subjectivity and subjection. Drawing on theories of power and the creation of subjects, Cruikshank argues that individuals in a democracy are made into self-governing citizens through the small-scale and everyday practices of voluntary associations, reform movements, and social service programs. She argues that our empowerment is a measure of our subjection rather than of our autonomy from power. Through a close examination of several contemporary American "technologies of citizenship"--Welfare rights struggles to philanthropic self-help schemes to the organized promotion of self-esteem awareness-she demonstrates how social mobilization reshapes the political in ways largely unrecognized in democratic theory. Although the impact of a given reform movement may be minor, the techniques it develops for creating citizens far extend the reach of govermental authority. Combining a detailed knowledge of social policy and practice with insights from poststructural and feminist theory, The Will to Empower shows how democratic citizens and the political are continually recreated.
Introduction: Small Things -- 1. Democratic Subjects -- 2. The Liberal Arts of Governance -- 3. The Will to Empower: Technologies of Citizenship and the War on Poverty -- 4. Revolutions Within: Self-Government and Self-Esteem -- 5. Welfare Queens: Ruling by Number -- Conclusion: Iteration.
First published 1999 by Cornell University Press. First printing, Cornell Paperbacks, 1999.
Includes bibliographical references and index.
In English.
Online resource; title from PDF title page (publisher's Web site, viewed 26. Nov 2019).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: Universidad Sergio Arboleda; Political participation -- United States; Democracy -- United States; Power (Social sciences) -- United States; Participation politique -- États-Unis.; Pouvoir (Sciences sociales) -- États-Unis.; PHILOSOPHY -- Political; Democracy; Political participation; Power (Social sciences); United States; Demokratie; Partizipation; Politische Beteiligung; USA; Political participation -- United States; Democracy -- United States; Power (Social sciences) -- United States